2002
DOI: 10.1614/0890-037x(2002)016[0231:hccdre]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hoary Cress (Cardaria draba) Root Extract Reduces Germination and Root Growth of Five Plant Species1

Abstract: The allelopathic potential of hoary cress was evaluated by exposing the seeds and the germinated seeds of winter wheat, alfalfa, crested wheatgrass, bluebunch wheatgrass, and hoary cress to a water extract of dried, hoary cress roots under controlled conditions in an environmental chamber. Germination for all species was reduced in the hoary cress root extract when compared with distilled water, with winter wheat and hoary cress being more tolerant than the other species. Root length of all species was reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…Biotic factors such as competition with other plants, below-ground interactions and also abiotic factors such as climate and soil properties could explain differences between the common greenhouse experiment and the natural situation. Studies are underway to test whether below-ground levels of glucosinolates and myrosinases might play a more important role as potential allelopathic agents, as suggested for L. draba (Qasem, 1994;Kiemnec and McInnis, 2002). The deviation from the tested predictions of the EICA hypothesis might be explained by the contrasting effect of defensive compounds on specialist vs. generalist herbivores, leading to an alternative hypothesis: specialisation by insects could make defence systems in native ranges less effective, and may even have disadvantages, as compared to the invasive range.…”
Section: Discussionmentioning
confidence: 99%
“…Biotic factors such as competition with other plants, below-ground interactions and also abiotic factors such as climate and soil properties could explain differences between the common greenhouse experiment and the natural situation. Studies are underway to test whether below-ground levels of glucosinolates and myrosinases might play a more important role as potential allelopathic agents, as suggested for L. draba (Qasem, 1994;Kiemnec and McInnis, 2002). The deviation from the tested predictions of the EICA hypothesis might be explained by the contrasting effect of defensive compounds on specialist vs. generalist herbivores, leading to an alternative hypothesis: specialisation by insects could make defence systems in native ranges less effective, and may even have disadvantages, as compared to the invasive range.…”
Section: Discussionmentioning
confidence: 99%
“…Qasem (1994) also found inhibitory effects of L. draba on germination, growth and development of wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.). Western US studies have shown that L. draba root extract slowed both the germination rate and initial root growth of alfalfa and forage grasses, but not winter wheat (Triticum aestivum), suggesting that L. draba may have a competitive advantage in forage areas through allelopathy (Kiemnec and McInnis 2002).…”
Section: Description and Account Of Variationmentioning
confidence: 99%
“…T base was 1 °C for A. fatua (Cousens et al, 1992) and 2.5 °C for D. sophia (Kiemnce & Mcinnis, 2002). This method is accurate if the minimum temperature is above the base temperature.…”
Section: Model Descriptionmentioning
confidence: 99%